COMPARATIVE EFFECTIVENBSS OF RELAXATION AND SYSTEMATIC DESENSITIZATION IN THE MANAGEMENT OF SPEECH ANXIETY (1984)
An experiment was designed to find out which of relaxation and systematic desensitization was more effective in the management of speech anxiety in Student teachers. A third measure of remediation - cognitive restructuring - was introduced as a control in this study to monitor the effect of cognition on speech anxiety. Its effectiveness was also compared with the other two management measures. A 4 x 2 factorial design was used in this study, The samples were taken from a group of 100 students in the post-school certificate class of a teachers' College. Results indicated that the systematic desensitization and cognitive restructuring procedures proved very effective in significantly reducing speech anxiety in most of the variables used in this study. The variables are the Stimulus response (SRI) inventory (F = 6.10, df = 3/40, P <.01), check-list questionnaire ( = 8.08, df = 3/40, P< .01), the pulse rate differential (F = 8.11, df = 3/40, P <.01 and speech rating (F = 2.48, df = 3/40). The systematic desensitization procedure was however more effective than the cognitive restructuring procedure. T - Values recorded on two of the variables used in the study are 6.41 (SRI) at df = 10 and P<.01, and 2.75 (CLQ) at df = 10 and P<.05. The relaxation measure was not as effective in managing speech anxiety as the earlier two measures. Though it reduced the anxiety level of the subjects, the relaxation measure was not significant even at the .05 probability level.